PENGARUH LABA OPERASI, ARUS KAS OPERASI, STUKTUR KEPEMILIKAN DAN STRUKTUR MODAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR BIDANG MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2010-2012 - JANSEN MARIN MARTUA HS; Zirman Zirman; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The title of this study research: "The Influence of operating profit, operation cash flow, ownership structure and capital structure to dividend policy on Food and Drink companies listed on the Stock Exchange from 2010 - 2012. In order to test the effect of multiple linear regression test was used. The purpose of this research is to determine the influence of each independent variable on the dependent variable partially and simultaneously. Furthermore, to determine among the 4 independent variables in this study, which is the most dominant Influence dependent variable. Effect of operating profit (X1), operation cash flow (X2), ownership structure (X3) and capital structure (X4) partially on the company's dividend policy food and drink ie 5.837E-006 for operating profit, 2.578E-006 for operation cash flow, 50.989 for ownership structure , and 6.070 for capital structure, the constant value of 39.679. Determinant coefficient (R2) showed 0.583. As a suggestion in this study (1) for potential investors before investing should seek out the company profile because it involves the performance of the company. (2) Investors should pay attention to operating profit and capital structure of the company who have a significant effect on dividend policy. (3) For further research is recommended to measure the influence of other variables besides independent variables in this study.Keywords : Operating Profit, Operation Cash Flow, Ownership Structure, Capital Structure, Dividend Policy, Company Food and Drink